2022
DOI: 10.3389/fphys.2022.816959
|View full text |Cite
|
Sign up to set email alerts
|

Glucocorticoid Receptor Maintains Vasopressin Responses in Kidney Collecting Duct Cells

Abstract: Water permeability of the kidney collecting ducts is regulated in part by the amount of the molecular water channel protein aquaporin-2 (AQP2), whose expression, in turn, is regulated by the pituitary peptide hormone vasopressin. We previously showed that stable glucocorticoid receptor knockdown diminished the vasopressin-induced Aqp2 gene expression in the collecting duct cell model mpkCCD. Here, we investigated the pathways regulated by the glucocorticoid receptor by comparing transcriptomes of the mpkCCD ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 75 publications
0
4
0
Order By: Relevance
“…Our current knowledge of kidney (patho)physiology is mainly derived from conventional research models that remain insufficient to fully elucidate certain mechanisms of kidney (patho)physiology ( Jung and Kwon, 2016 ; Edwards and Crambert, 2017 ; Kleyman and Eaton, 2019 ). And even though many models have been described, they often lack endogenous expression of relevant ion channels and transporters that are subject to physiological regulation ( Yang et al, 2022 ). Therefore, we have created tubuloids derived from mouse kidney tissue that are differentiated towards the CD, show physiological channel regulation and functional ion uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Our current knowledge of kidney (patho)physiology is mainly derived from conventional research models that remain insufficient to fully elucidate certain mechanisms of kidney (patho)physiology ( Jung and Kwon, 2016 ; Edwards and Crambert, 2017 ; Kleyman and Eaton, 2019 ). And even though many models have been described, they often lack endogenous expression of relevant ion channels and transporters that are subject to physiological regulation ( Yang et al, 2022 ). Therefore, we have created tubuloids derived from mouse kidney tissue that are differentiated towards the CD, show physiological channel regulation and functional ion uptake.…”
Section: Discussionmentioning
confidence: 99%
“…Epac-dependent Ca 2+ mobilization was associated with AVP-induced apical exocytosis in perfused IMCD. mpkCCD cells have been used as the cell model for transcriptomic and phosphoproteomic studies of AVP-signaling in the collecting duct ( Rinschen et al, 2010 ; Huling et al, 2012 ; Sandoval et al, 2013 ; Yang et al, 2022 ; Park et al, 2023 ). We have demonstrated that mpkCCD cells retain the characteristics of Epac-dependent Ca 2+ mobilization as in intact IMCD cells.…”
Section: Discussionmentioning
confidence: 99%
“…Murine principal kidney cortical collecting duct (mpkCCD) cells are commonly used cell model used for transcriptomic and phosphoproteomic studies of AVP-signaling in kidney collecting ducts ( Rinschen et al, 2010 ; Huling et al, 2012 ; Sandoval et al, 2013 ; Yang et al, 2022 ; Park et al, 2023 ). It is assumed that mpkCCD cell retains the feature of intact collecting duct cell in AVP-induced signaling events of AQP2 trafficking.…”
Section: Introductionmentioning
confidence: 99%
“…Peripheral actions of glucocorticoids also affect water balance. In vitro studies of collecting duct cells suggest that glucocorticoids enhance AVP-dependent transcription of aquaporin-2 (AQP2) [26], likely due to a glucocorticoid-responsive element in the AQP2 gene promotor region [27]. In contrast, in vivo studies have demonstrated that AQP2 expression is elevated in states of glucocorticoid deficiency [28, 29].…”
Section: The Hypothalamic-pituitary-adrenal Axis and Water Balancementioning
confidence: 99%